Factorial Grothendieck Polynomials - McNamara, Peter J. (The Electronic Journal of Combinatorics, 2006)
In this paper, we study Grothendieck polynomials indexed by Grassmannian permutations from a combinatorial viewpoint. We introduce the factorial Grothendieck polynomials which are analogues of the factorial Schur functions, study their properties, and use them to produce a generalisation of a Littlewood-Richardson rule for Grothendieck polynomials.